1714 Ability of Self-Inflating Bags (SIB) to Deliver Sustained Inflations. (October 2012) - Thio, M; Dawson, JA; Moss, TJ; Hooper, SB; Davis, PG
Abstract : Background and Aims: In neonatal resuscitation, the use of a sustained inflation (SI) after birth may facilitate lung recruitment. We aimed to assess the ability of several SIB to deliver a SI. Method: In a newborn preterm lamb, we compared 4 different SIB devices fitted with a PEEP valve against a T-piece, using a flow of 8 Lpm. Four operators aimed to give 3 targeted SI of 20 cmH2 O (displayed on a manometer) for 30 seconds. The study was repeated with the PEEP valve removed and again with no flow. Results: 204 combinations were analysed. Mean (SD) duration of SI, maximum inspiratory pressure (maximum IP) and average inspiratory pressure (average IP) are shown in the table . PEEP valve removal and absence of flow made no significant difference to the SI time (P=0.34 and P=0.13 respectively), maximum IP (P=0.17 and P=0.12 respectively) or average IP (P=0.32 and P=0.60 respectively). Conclusions: SIB perform differently depending on the brand and some are able to deliver sustained SI even in the absence of gas flow. If medically indicated, this may be useful in a resource-limited setting with no gas supply.